Integrative analysis of metabolite and transcriptome reveals biosynthetic pathway and candidate genes for eupatilin and jaceosidin biosynthesis in Artemisia argyi - Lee, Suhyeon; Won, Hyo Jun; Ban, Seunghyun; Park, Yun Ji; Kim, Sang Min; Kim, Hyoung Seok; Choi, Jaeyoung; Kim, Ho-Youn; Lee, Jae Hoon; Jung, Je Hyeong (Frontiers in Plant Science, 2023)
Artemisia argyi (A. argyi) is a medicinal plant that belongs to the Asteraceae family and Artemisia genus. The Artemisia genus includes over 500 species and owing to various components, is widely used in tea, food, and pharmaceutical industries. The leaves of A. argyi contain abundant flavonoids, which are representative secondary metabolites responsible for anti-inflammatory, anticancer, and antioxidative effects. Among these flavonoids, eupatilin and jaceosidin are representative polymethoxy flavonoids, have medicinal properties that are significant enough to warrant the development of drugs using their components. However, the biosynthetic pathways and related genes of these compounds in A. argyi have not been fully explored. In this study, we comprehensively analyzed the transcriptome data and flavonoids from the young leaves, old leaves, trichomes, and stems (without trichomes) of A. argyi. Based on the flavonoids and their chemical structures, we proposed a biosynthetic pathway for eupatilin and jaceosidin. We obtained 41,398 unigenes via de-novo assembly of transcriptome data and mined candidate genes related to the biosynthesis of eupatilin and jaceosidin using differentially expressed genes, clustering, a phylogenetic tree, and weighted gene co-expression analysis. As a result, we identified five flavone-6-hydroxylase (F6H) genes, one flavone synthase (FNS) I gene, one FNS II gene, four flavonoid 3'-O-methyltransferase (F3'OMT) genes, and one F4'OMT and/or F6OMT gene that are crucial for the biosynthesis of eupatilin and jaceosidin. We expect that the results of this study will serve as a foundation for the use of synthetic biology for the mass production of eupatilin and jaceosidin.